Administration of Methotrexate in Rheumatoid Arthritis Patients with Chronic Hepatitis B - Velma Herwanto; Andri Sanityoso (The Indonesian Society for Digestive Endoscopy, 2015)
Aim: To identify if methotrexate (MTX) may be given to chronic hepatitis B patients and to evaluate the necessity of antiviral prophylaxis administration.Method: Literature search procedure to answer this clinical problem was performed by exploring the literature online using PubMed, Highwire Stanford University, NUS Library, and MD Consult search engines. With this searching method, we found 20 articles in English. From those 20 articles, there were two articles relevant based on the title and abstract (studies by Tamori et al and Mori).Results: From 45 patients without HbsAg from Tamori et al study, only one from 3 patients receiving disease-modifying antirheumatoid drug/DMARD (including MTX) experienced reactivation. Those three patients did not receive anti-TNF-α therapy. Study by Mori concluded that DMARD was relatively safe to be given to most RA patients with the history of HBV infection, although they were not given anti HBV prophylaxis therapy.Conclusion: MTX is not recommended for patient in this case because it is contraindicated to be given in HBV infected patient with any given Child Pugh score. If MTX is still given, it is recommended to give antiviral prophylaxis therapy.